The Investigation of Magnetic Field Distribution of Dual Coil Pulsed Magnet - Bartkevičius, S.; Novickij, J. (Elektronika ir Elektrotechnika, 2009)
The evaluation of magnetic field distribution of dual coil pulsed magnet has been performed. Coil geometry was found by the simulation of transient electromagnetic, magneto mechanical ant thermodynamic processes using Matlab Simulink and Matlab software. The result of optimization has allowed to determine of coil “life-zone” where the maximum mechanical stress and temperature do not exceed the yield strength and thermal overloads limits. The distance between parts of dual coil has been determined from the minimum field distortion criteria in centre of dual coil. The non-homogeneity of magnetic field does not exceed 0,01% in 10 mm central area. Ill. 5, bibl. 9 (in English; summaries in English, Russian and Lithuanian).